Estudio Ambiental como Mecanismo de Sostenibilidad del Proyecto de Instalación de la Fábrica de Ladrillos de Arcilla al Vacío en Habana Distrito de Moyobamba, San Martín - Perú. - García Panduro, Jorge Miguel (2011)
The present study, classified according to the screening of the project, is a semidetallado environmental study; Becoming an instrument that describes, analyzes the activities of the brick making process, from the extraction of the clays and their impact; The transformation of matter and the mechanisms it intends to use, for the operation of the process. All this, taking into account the location of plant, geographical area of the market, reserve of raw material and economic and financial support of the company to execute the project. Then through the environmental study as a mechanism of sustainability, present the management plan, monitoring, and with its measures, contemplate the mitigation, correction and other impacts to the future to provoke by the development of the activity, in the perfectible way , And the company's commitment to the environment; For the viability of the activity in a sustained way.